EVALUASI KEPATUHAN GOOD CORPORATE GOVERNANCE TERHADAP ASEAN CORPORATE GOVERNANCE STUDI PADA CONSUMER GOODS INDUSTRY YANG TERDAFTAR DI BURSA EFEK INDONESIA - Jennifer Karina; Weli Weli (Magister Akuntansi, Universitas Atma Jaya Makassar, 2020)
This research is analyzing the score of Indonesia Stock Exchange listed corporations under consumer goods industry sector’s compliance on Good Corporate Governance using ASEAN Corporate Governance. Data used are originated from corporations’ annual reports, financial report, and publicly-accessed information in the period of 2018 over 32 consumer goods corporations. The data gathered was processed through Microsoft Excel. Results show that on consumer goods industry’s corporations, there are three good corporate governance principles (Rights of Shareholders, Equitable Treatment of Shareholders, Responsibilities of the Board) scored not more than 50%, while the other two (Role of Stakeholders, Disclosure and Transparency ) have achieved the score of over 50% of the overall points of recommendations.